Influence of process parameters on the formation of inhalable fiber dust during shredding for mechanical recycling of fiber‐reinforced organo sheets - Hopp, Matthias; Tölle, Lisa (Journal of Applied Polymer Science)

Fiber Dust Formation during the Recycling of FRP - Hopp, Matthias; Tölle, Lisa; Bünger, J.; Westphal, G.; Rosenkranz, N.; Monsé, C. (Kunststoffe international)

Faserstäube beim FVK-Recycling - Hopp, Matthias; Tölle, Lisa; Bünger, J.; Westphal, G.; Rosenkranz, N.; Monsé, C. (Kunststoffe)

Computation on Encrypted Data Using Dataflow Authentication - Fischer, Andreas; Fuhry, Benny; Kußmaul, Jörn; Janneck, Jonas; Kerschbaum, Florian; Bodden, Eric (ACM Transactions on Privacy and Security)
Encrypting data before sending it to the cloud ensures data confidentiality but requires the cloud to compute on encrypted data. Trusted execution environments, such as Intel SGX enclaves, promise to provide a secure environment in which data can be decrypted and then processed. However, vulnerabilities in the executed program give attackers ample opportunities to execute arbitrary code inside the enclave. This code can modify the dataflow of the program and leak secrets via SGX side channels. Fully homomorphic encryption would be an alternative to compute on encrypted data without data leaks. However, due to its high computational complexity, its applicability to general-purpose computing remains limited. Researchers have made several proposals for transforming programs to perform encrypted computations on less powerful encryption schemes. Yet current approaches do not support programs making control-flow decisions based on encrypted data. We introduce the concept of dataflow authentication (DFAuth) to enable such programs. DFAuth prevents an adversary from arbitrarily deviating from the dataflow of a program. Our technique hence offers protections against the side-channel attacks described previously. We implemented two flavors of DFAuth, a Java bytecode-to-bytecode compiler, and an SGX enclave running a small and program-independent trusted code base. We applied DFAuth to a neural network performing machine learning on sensitive medical data and a smart charging scheduler for electric vehicles. Our transformation yields a neural network with encrypted weights, which can be evaluated on encrypted inputs in \( 12.55 \,ms \) . Our protected scheduler is capable of updating the encrypted charging plan in approximately 1.06 seconds.
Keywords: Safety; Risk; Reliability and Quality; General Computer Science

Conditional Beta-Convergence by Gravity - Stöckmann, Nico (Theoretical Economics Letters)

Verteiltes Berechnen kompakter Routingtabellen in Unit Disk Graphen - Hillebrandt, Henning

Realization of Exciton‐Mediated Optical Spin‐Orbit Interaction in Organic Microcrystalline Resonators - Ren, Jiahuan; Liao, Qing; Ma, Xuekai; Schumacher, Stefan; Yao, Jiannian; Fu, Hongbing (Laser & Photonics Reviews)

Controlling exciton distribution in WS2 monolayer on a photonic crystal - Zhang, Xiu; Chen, Zhenshi; Liu, Dong; Wan, Lei; Ma, Xuekai; Gao, Tingge (Applied Physics Express)

Dynamics of phase defects trapped in optically imprinted orbits in dissipative binary polariton condensates - Wingenbach, Jan; Pukrop, Matthias; Schumacher, Stefan; Ma, Xuekai (Physical Review B)

The Ruelle zeta function at zero for nearly hyperbolic 3-manifolds - Cekić, Mihajlo; Delarue, Benjamin; Dyatlov, Semyon; Paternain, Gabriel P. (Inventiones mathematicae)
Abstract We show that for a generic conformal metric perturbation of a compact hyperbolic 3-manifold $$Σ $$ Σ with Betti number $$b_1$$ b 1 , the order of vanishing of the Ruelle zeta function at zero equals $$4-b_1$$ 4 - b 1 , while in the hyperbolic case it is equal to $$4-2b_1$$ 4 - 2 b 1 . This is in contrast to the 2-dimensional case where the order of vanishing is a topological invariant. The proof uses the microlocal approach to dynamical zeta functions, giving a geometric description of generalized Pollicott–Ruelle resonant differential forms at 0 in the hyperbolic case and using first variation for the perturbation. To show that the first variation is generically nonzero we introduce a new identity relating pushforwards of products of resonant and coresonant 2-forms on the sphere bundle $$SΣ $$ S Σ with harmonic 1-forms on $$Σ $$ Σ .
Keywords: General Mathematics

Remote epitaxy of InxGa1-xAs (0 0 1) on graphene covered GaAs(0 0 1) substrates - Henksmeier, T.; Schulz, J.F.; Kluth, E.; Feneberg, M.; Goldhahn, R.; Sanchez, A.M.; Voigt, M.; Grundmeier, Guido; Reuter, Dirk (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Influence of curing-induced pre-deformations on the mechanical properties of adhesively bonded joints in steel-intensive mixed-material structures - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson; Aubel, Tobias; Matzenmiller, Anton (Proceedings of the 6th Conference on Steels in Cars and Trucks)

Early time behavior of spatial and momentum anisotropies in kinetic theory across different Knudsen numbers - Borghini, Nicolas; Borrell, Marc; Roch, Hendrik (arXiv:2201.13294)
We investigate the early time development of the anisotropic transverse flow and spatial eccentricities of a fireball with various particle-based transport approaches using a fixed initial condition. In numerical simulations ranging from the quasi-collisionless case to the hydrodynamic regime, we find that the onset of $v_n$ and of related measures of anisotropic flow can be described with a simple power-law ansatz, with an exponent that depends on the amount of rescatterings in the system. In the few-rescatterings regime we perform semi-analytical calculations, based on a systematic expansion in powers of time and the cross section, which can reproduce the numerical findings.

A review of 100% renewable energy scenarios on islands - Meschede, Henning; Bertheau, Paul; Khalili, Siavash; Breyer, Christian (WIREs Energy and Environment)
Keywords: General Environmental Science; Renewable Energy; Sustainability and the Environment

Even anisotropic-flow harmonics are from Venus, odd ones are from Mars - Bachmann, Benedikt; Borghini, Nicolas; Feld, Nina; Roch, Hendrik (arXiv:2203.13306)
We test the ability of the "escape mechanism" to create the anisotropic flow observed in high-energy nuclear collisions. We compare the flow harmonics $v_n$ in the few-rescatterings regime from two types of transport simulations, with $2→ 2$ and $2→ 0$ collision kernels respectively, and from analytical calculations neglecting the gain term of the Boltzmann equation. We find that the even flow harmonics are similar in the three approaches, while the odd harmonics differ significantly.

Linearly shifting ferromagnetic resonance response of La0.7Sr0.3MnO3 thin film for body temperature sensors - Hou, W; Yao, Y; Li, Y; Peng, B; Shi, K; Zhou, Z; Pan, J; Liu, M; Hu, J (Frontiers of materials science)

Dataset for random uniform distributions of 2D circles and 3D spheres. - Wojciechowski, M (Data Brief)

Pattern formation in a four-ring reaction-diffusion network with heterogeneity. - Hunter, I; Norton, MM; Chen, B; Simonetti, C; Moustaka, ME; Touboul, J; Fraden, S (Phys Rev E)

Reversible functionalization and exfoliation of graphite by a Diels–Alder reaction with furfuryl amine - Filvan Torkaman, Najmeh; Kley, Marina; Bremser, Wolfgang; Wilhelm, René (RSC Advances)
Furfuryl amine-functionalized few-layered graphene was prepared via a mechanochemical process by a [4 + 2] cycloaddition under solvent-free conditions.
Keywords: General Chemical Engineering; General Chemistry

Perception of Society’s Trust in Care Robots by Public Opinion Leaders - Hoppe, Julia Amelie; Melkas, Helinä; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Thommes, Kirsten (International Journal of Human–Computer Interaction)
Keywords: Computer Science Applications; Human-Computer Interaction; Human Factors and Ergonomics

Perception of Society’s Trust in Care Robots by Public Opinion Leaders - Hoppe, Julia Amelie; Melkas, Helinä; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Thommes, Kirsten (International Journal of Human–Computer Interaction)
Keywords: Computer Science Applications; Human-Computer Interaction; Human Factors and Ergonomics

Losing What You Never Had - Akkerman, Agnes; Manevska, Katerina; Thommes, Kirsten; Sluiter, Roderick (Employment Relations as Networks)

Investigation of leak tightness for bonded steel joints induced by mechanical and corrosive load for use in battery housings - Schmolke, Tobias; Meschut, Gerson (Proceedings of the 6th Conference on Steels in Cars and Trucks)

Three Layers of Abstraction—A Conceptual Framework for Theorizing digital Multi-Sided Platforms - Poniatowski, Martin; Lüttenberg, Hedda; Beverungen, Daniel; Kundisch, Dennis (Information Systems and e-Business Management, Special Issue on Platform Business Models and Platform Strategies)

Property-Driven Testing of Black-Box Functions - Sharma, Arnab; Melnikov, Vitaly; Hüllermeier, Eyke; Wehrheim, Heike (Proceedings of the 10th IEEE/ACM International Conference on Formal Methods in Software Engineering (FormaliSE))
Testing is one of the most frequent means of quality assurance for software. Property-based testing aims at generating test suites for checking code against user-defined properties. Test input generation is, however, most often independent of the property to be checked, and is instead based on random or user-defined data generation.In this paper, we present property-driven unit testing of functions with numerical inputs and outputs. Alike property-based testing, it allows users to define the properties to be tested for. Contrary to property-based testing, it also uses the property for a targeted generation of test inputs. Our approach is a form of learning-based testing where we first of all learn a model of a given black-box function using standard machine learning algorithms, and in a second step use model and property for test input generation. This allows us to test both predefined functions as well as machine learned regression models. Our experimental evaluation shows that our property-driven approach is more effective than standard property-based testing techniques.

Model-driven Continuous Experimentation on Component-based Software Architectures - Gottschalk, Sebastian; Yigitbas, Enes; Engels, Gregor (Proceedings of the 18th International Conference on Software Architecture Companion)
To build successful software products, developers continuously have to discover what features the users really need. This discovery can be achieved with continuous experimentation, testing different software variants with distinct user groups, and deploying the superior variant for all users. However, existing approaches do not focus on explicit modeling of variants and experiments, which offers advantages such as traceability of decisions and combinability of experiments. Therefore, our vision is the provision of model-driven continuous experimentation, which provides the developer with a framework for structuring the experimentation process. For that, we introduce the overall concept, apply it to the experimentation on component-based software architectures and point out future research questions. In particular, we show the applicability by combining feature models for modeling the software variants, users, and experiments (i.e., model-driven) with MAPE-K for the adaptation (i.e., continuous experimentation) and implementing the concept based on the component-based Angular framework.
Keywords: continuous experimentation; model-driven; component-based software architectures; self-adaptation

„Beim Ausschneiden zeigen die Wörter mir ihre Bestandteile.“ Memoria als Deutungsöffnung bei Herta Müller - Kißling, Magdalena (Der Deutschunterricht (1))

Bildungsverantwortung im Deutschunterricht. Thesen zu einem bildungsgerechten Literaturunterricht - Kißling, Magdalena (IMST-Newsletter (53))

Influence of hydrogel coatings on corrosion and fatigue of iron in simulated body fluid - Huang, Jingyuan; Voigt, Markus; Wackenrohr, Steffen; Ebbert, Christoph; Keller, Adrian; Maier, Hans Jürgen; Grundmeier, Guido (Materials and Corrosion)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry

Symmetrieverständnis von Anfang an - Häsel-Weide, Uta; Wallner, Melina; Hattermann, M. (Anfangsunterricht für alle Kinder - Willkommen in der Schule!)

Formation of insoluble silver-phases in an iron-manganese matrix for bioresorbable implants using varying laser beam melting strategies - Krüger, Jan Tobias; Hoyer, Kay-Peter; Hengsbach, Florian; Schaper, Mirko (Journal of Materials Research and Technology)
Keywords: Metals and Alloys; Surfaces; Coatings and Films; Biomaterials; Ceramics and Composites

Disjoining and repair strategies of structural joints in automotive lightweight structures - Chudalla, Nick; Bartley, Aurélie; Ditter, Jan; Meschut, Gerson; Wibbeke, Tim Michael

A PLACE FOR A DATA SCIENCE PROJECT IN SCHOOL: BETWEEN STATISTICS AND EPISTEMIC PROGRAMMING - PODWORNY, SUSANNE; Hüsing, Sven; SCHULTE, CARSTEN (STATISTICS EDUCATION RESEARCH JOURNAL)
Aspects of data science surround us in many contexts, for example regarding climate change, air pollution, and other environmental issues. To open the “data-science-black-box” for lower secondary school students we developed a data science project focussing on the analysis of self-collected environmental data. We embed this project in computer science education, which enables us to use a new knowledge-based programming approach for the data analysis within Jupyter Notebooks and the programming language Python. In this paper, we evaluate the second cycle of this project which took place in a ninth-grade computer science class. In particular, we present how the students coped with the professional tool of Jupyter Notebooks for doing statistical investigations and which insights they gained.
Keywords: Education; Statistics and Probability

Microinverter testing update using high power modules: Efficiency, yield, and conformity to a new ”estimation formula” for variation of PV panel size - Krauter, Stefan; Bendfeld, Jörg; Möller, Marius Claus (Proceedings of the 49th IEEE Photovoltaic Specialists Conference)
The market for microinverters is growing, especially in Europe. Driven by the strongly rising prices for electricity, many small photovoltaic energy systems are being installed. Since monitoring for these plants is often quite costly, their yields are often not logged. Since 2014, microinverters have been studied at the University of Paderborn. The investigations are divided into indoor and outdoor tests. In the indoor area conversion efficiencies as a function of load have been measured with high accuracy and ranked according to Euro- and CEC weightings. In the outdoor laboratory, the behavior in the real world is tested. Energy yields have been measured outdoors via identical and calibrated crystalline silicon PV modules. Here, the investigations were carried out with modules of the power of 215 Wp until the year 2020. Because of the increasing module power nowadays, modules with an output of 360 Wp are now being used. To assess the influence of PV module size, two extremes have been investigated: A rather small module with 215 Wp - as it has been used 10 years ago, and a brand-new module (2021) offering 360 Wp. Both types of modules contain 60 solar cells in series connection. Appling the low-power modules, the challenge for the different micro-inverters has been during weak-light conditions, using the high-power modules, some inverters temporarily reach their power limits and yield is reduced. A method using a reference configuration of inverter & module and a linear equation resulting in the actual yield, any module & inverter configuration can be characterized by just the two coefficients.

Professionalisierung für inklusiven Mathematikunterricht. Interdisziplinäre Seminarkonzeption zur reflexiven Professionalisierung angehender Mathematiklehrkräfte in der Sekundarstufe - Häsel-Weide, Uta; Seitz, S.; Wallner, Melina; Wilke, Y. (Qualifizierung für Inklusion. Sekundarstufe)

Diagnosegeleitete Förderung im inklusiven Mathematikunterricht der Grundschule – Professionalisierung durch reflektierte Handlungspraxis in der Lehrer*innenbildung. - Hähn, K.; Häsel-Weide, Uta; Scherer, P. (QfI - Qualifizierung für Inklusion)

Model of a Self-Sufficient PV Home using a Hybrid Storage System based on Li-Ion Batteries and Hydrogen Storage with Waste Heat Utilization - Möller, Marius Claus; Krauter, Stefan (Proceedings of the 49th IEEE Photovoltaic Specialists Conference)
This paper provides a hybrid energy system model created in Matlab/Simulink which is based on photovoltaics as its main energy source. The model includes a hybrid energy storage which consists of a short-term lithium-ion battery and hydrogen as long-term storage to ensure autonomy even during periods of low PV production (e.g., in winter). The sectors heat and electricity are coupled by using the waste-heat generated by production and reconversion of hydrogen through an electrolyser respectively a fuel cell. A heat pump has been considered to cover the residual heat demand (for well insulated homes). Within this paper a model of the space heating system as well as the hot water heating system is presented. The model is designed for the simulation and analysis of a whole year energy flow by using a time series of loads, weather and heat profiles as input. Moreover, results of the energy balance within the energy system by simulation of a complete year by varying the orientation (elevation and azimuth) of the PV system and the component sizing, such as the lithium-ion battery capacity, are presented. It turned out that a high amount of heating energy can be saved by using the waste heat generated by the electrolyser and the fuel cell. The model is well suited for the analysis of the effects of different component dimensionings in a hydrogen-based energy system via the overall energy balance within the residential sector.

Hybrid Energy System Model in Matlab/Simulink based on Solar Energy, Lithium-Ion Battery and Hydrogen - Möller, Marius Claus; Krauter, Stefan (Energies / Special Issue "Sustainable Energy Concepts for Energy Transition")
In this paper, a model of a hybrid, hydrogen-based energy system for a household which includes the heating sector is presended. With such an energy system it's possible to enable energy autarky over a whole year based on solar energy. The scope of this study was to present a verified hybrid energy system model created in Simulink which can be used to prospectively size future similar energy systems where hydrogen in combination with a li-ion battery shall be used as energy storage type.

Increased Cognitive Demands Affect Agility Performance in Female Athletes - Implications for Testing and Training of Agility in Team Ball Sports - Büchel, Daniel; Gokeler, Alli; Heuvelmans, Pieter; Baumeister, Jochen (Perceptual and Motor Skills)
Agility, a key component of team ball sports, describes an athlete´s ability to move fast in response to changing environments. While agility requires basic cognitive functions like processing speed, it also requires more complex cognitive processes like working memory and inhibition. Yet, most agility tests restrict an assessment of cognitive processes to simple reactive times that lack ecological validity. Our aim in this study was to assess agility performance by means of total time on two agility tests with matched motor demands but with both low and high cognitive demands. We tested 22 female team athletes on SpeedCourt, using a simple agility test (SAT) that measured only processing speed and a complex agility test (CAT) that required working memory and inhibition. We found excellent to good reliability for both our SAT (ICC = .79) and CAT (ICC =.70). Lower agility performance on the CAT was associated with increased agility total time and split times ( p < .05). These results demonstrated that agility performance depends on the complexity of cognitive demands. There may be interference-effects between motor and cognitive performances, reducing speed when environmental information becomes more complex. Future studies should consider agility training models that implement complex cognitive stimuli to challenge athletes according to competitive demands. This will also allow scientists and practitioners to tailor tests to talent identification, performance development and injury rehabilitation.
Keywords: Sensory Systems; Experimental and Cognitive Psychology

Smart Service für die prädiktive Instandhaltung zentraler Komponenten des Mittelspannungs-Netzes - zur Heiden, Philipp; Priefer, Jennifer; Beverungen, Daniel (Forum Dienstleistungsmanagement)

Method development for increasing the prediction quality of mechanical joining process simulations by friction modeling based on local joining process parameters - Rossel, Moritz Sebastian; Meschut, Gerson (Proceedings of the 6th Conference on Steels in Cars and Trucks)

Koopman analysis of quantum systems - Klus, Stefan; Nüske, Feliks; Peitz, Sebastian (Journal of Physics A: Mathematical and Theoretical)
Koopman operator theory has been successfully applied to problems from various research areas such as fluid dynamics, molecular dynamics, climate science, engineering, and biology. Applications include detecting metastable or coherent sets, coarse-graining, system identification, and control. There is an intricate connection between dynamical systems driven by stochastic differential equations and quantum mechanics. In this paper, we compare the ground-state transformation and Nelson's stochastic mechanics and demonstrate how data-driven methods developed for the approximation of the Koopman operator can be used to analyze quantum physics problems. Moreover, we exploit the relationship between Schrödinger operators and stochastic control problems to show that modern data-driven methods for stochastic control can be used to solve the stationary or imaginary-time Schrödinger equation. Our findings open up a new avenue towards solving Schrödinger's equation using recently developed tools from data science.

CamBench -- Cryptographic API Misuse Detection Tool Benchmark Suite - Schlichtig, Michael; Wickert, Anna-Katharina; Krüger, Stefan; Bodden, Eric; Mezini, Mira
Context: Cryptographic APIs are often misused in real-world applications. Therefore, many cryptographic API misuse detection tools have been introduced. However, there exists no established reference benchmark for a fair and comprehensive comparison and evaluation of these tools. While there are benchmarks, they often only address a subset of the domain or were only used to evaluate a subset of existing misuse detection tools. Objective: To fairly compare cryptographic API misuse detection tools and to drive future development in this domain, we will devise such a benchmark. Openness and transparency in the generation process are key factors to fairly generate and establish the needed benchmark. Method: We propose an approach where we derive the benchmark generation methodology from the literature which consists of general best practices in benchmarking and domain-specific benchmark generation. A part of this methodology is transparency and openness of the generation process, which is achieved by pre-registering this work. Based on our methodology we design CamBench, a fair "Cryptographic API Misuse Detection Tool Benchmark Suite". We will implement the first version of CamBench limiting the domain to Java, the JCA, and static analyses. Finally, we will use CamBench to compare current misuse detection tools and compare CamBench to related benchmarks of its domain.
Keywords: cryptography; benchmark; API misuse; static analysis

Chancen für einen rassismussensiblen Literaturunterricht - didaktische Perspektiven für das Lesen von Menschenzoogeschichten in der Grundschule am Beispiel von Rainer Maria Rilkes Gedicht "Die Aschanti. Jardin d´acclimatation" (1902) - Tönsing, Johanna (Rassismussensibler Literaturunterricht. Neue Perspektiven einer kulturwissenschaftlichen Literaturdidaktik)

(K)eine kinderleichte Gattung: Konsequenzen einer kulturwissenschaftlich informierten Märchendidaktik - Tönsing, Johanna (Interpretationsverfahruen der germanistischen Literaturdidaktik und didaktische Referenzkonzepte)

Bringing Massive Parallelism and Hardware Acceleration to Linear Scaling Density Functional Theory Through Targeted Approximations - Lass, Michael

Über „Gleis 11“ [Dokumentarfilm von 2021] - Tönsing, Johanna (Sammelband über den deutsch-türkischen Film)

Weiblichkeitsdiskurse in der Gegenwartsliteratur und deren Thematisierung im genderorientierten Unterricht - Tönsing, Johanna (Neue Perspektiven einer kulturwissenschaftlichen Literaturdidaktik)

A Large-Scale Study of Usability Criteria Addressed by Static Analysis Tools - Nachtigall, Marcus; Schlichtig, Michael; Bodden, Eric (Proceedings of the 31st ACM SIGSOFT International Symposium on Software Testing and Analysis)
Static analysis tools support developers in detecting potential coding issues, such as bugs or vulnerabilities. Research on static analysis emphasizes its technical challenges but also mentions severe usability shortcomings. These shortcomings hinder the adoption of static analysis tools, and in some cases, user dissatisfaction even leads to tool abandonment. To comprehensively assess the current state of the art, this paper presents the first systematic usability evaluation in a wide range of static analysis tools. We derived a set of 36 relevant criteria from the scientific literature and gathered a collection of 46 static analysis tools complying with our inclusion and exclusion criteria - a representative set of mainly non-proprietary tools. Then, we evaluated how well these tools fulfill the aforementioned criteria. The evaluation shows that more than half of the considered tools offer poor warning messages, while about three-quarters of the tools provide hardly any fix support. Furthermore, the integration of user knowledge is strongly neglected, which could be used for improved handling of false positives and tuning the results for the corresponding developer. Finally, issues regarding workflow integration and specialized user interfaces are proved further. These findings should prove useful in guiding and focusing further research and development in the area of user experience for static code analyses.
Keywords: Automated static analysis; Software usability

FUM - A Framework for API Usage constraint and Misuse Classification - Schlichtig, Michael; Sassalla, Steffen; Narasimhan, Krishna; Bodden, Eric (2022 IEEE International Conference on Software Analysis, Evolution and Reengineering (SANER))
Application Programming Interfaces (APIs) are the primary mechanism that developers use to obtain access to third-party algorithms and services. Unfortunately, APIs can be misused, which can have catastrophic consequences, especially if the APIs provide security-critical functionalities like cryptography. Understanding what API misuses are, and for what reasons they are caused, is important to prevent them, e.g., with API misuse detectors. However, definitions and nominations for API misuses and related terms in literature vary and are diverse. This paper addresses the problem of scattered knowledge and definitions of API misuses by presenting a systematic literature review on the subject and introducing FUM, a novel Framework for API Usage constraint and Misuse classification. The literature review revealed that API misuses are violations of API usage constraints. To capture this, we provide unified definitions and use them to derive FUM. To assess the extent to which FUM aids in determining and guiding the improvement of an API misuses detectors' capabilities, we performed a case study on CogniCrypt, a state-of-the-art misuse detector for cryptographic APIs. The study showed that FUM can be used to properly assess CogniCrypt's capabilities, identify weaknesses and assist in deriving mitigations and improvements. And it appears that also more generally FUM can aid the development and improvement of misuse detection tools.
Keywords: API misuses; API usage constraints; classification framework; API misuse detection; static analysis

Modelling and Proving Security for a Secure MPC Protocol for Stable Matching - Vahle, Ella

Visualisierung von Ultraschallfeldern mittels Schlierentechnik und fraktionaler Fouriertransformation - Hetkämper, Tim

Messverfahren für die akustische Absorption zur Bestimmung der Volumenviskosität - Claes, Leander

Heat regeneration model for external heat engines operating with dense working fluids - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny (Annual Meeting on Reaction Engineering and ProcessNet Subject Division Heat and Mass Transfer)

The k-Server with Preferences Problem - Castenow, Jannik; Feldkord, Björn; Knollmann, Till; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (Proceedings of the 34th ACM Symposium on Parallelism in Algorithms and Architectures)
The famous $k$-Server Problem covers plenty of resource allocation scenarios, and several variations have been studied extensively for decades. However, to the best of our knowledge, no research has considered the problem if the servers are not identical and requests can express which specific servers should serve them. Therefore, we present a new model generalizing the $k$-Server Problem by *preferences* of the requests and proceed to study it in a uniform metric space for deterministic online algorithms (the special case of paging). In our model, requests can either demand to be answered by any server (*general requests*) or by a specific one (*specific requests*). If only general requests appear, the instance is one of the original $k$-Server Problem, and a lower bound for the competitive ratio of $k$ applies. If only specific requests appear, a solution with a competitive ratio of $1$ becomes trivial since there is no freedom regarding the servers' movements. Perhaps counter-intuitively, we show that if both kinds of requests appear, the lower bound raises to $2k-1$. We study deterministic online algorithms in uniform metrics and present two algorithms. The first one has an adaptive competitive ratio dependent on the frequency of specific requests. It achieves a worst-case competitive ratio of $3k-2$ while it is optimal when only general or only specific requests appear (competitive ratio of $k$ and $1$, respectively). The second has a fixed close-to-optimal worst-case competitive ratio of $2k+14$. For the first algorithm, we show a lower bound of $3k-2$, while the second algorithm has a lower bound of $2k-1$ when only general requests appear. The two algorithms differ in only one behavioral rule for each server that significantly influences the competitive ratio. Each server acting according to the rule allows approaching the worst-case lower bound, while it implies an increased lower bound for $k$-Server instances. In other words, there is a trade-off between performing well against instances of the $k$-Server Problem and instances containing specific requests. We also show that no deterministic online algorithm can be optimal for both kinds of instances simultaneously.
Keywords: K-Server Problem; Heterogeneity; Online Caching

Künstliche Intelligenz fachfremd mittels Open Educational Resources unterrichten. Wie das Flipped-Classroom-Format bei der Einbettung in die Lehre der Anglistik hilft. - Mindt, Ilka (Künstliche Intelligenz mit offenen Lernangeboten an Hochschulen lehren. Erfahrungen und Erkenntnisse aus dem Fellowship-Programm des KI-Campus.)

Blogpost "Nahtoderfahrungen und ihre Deutungen" - Lebock, Sarah
BloKK-Beitrag für das ZeKK, 04.02.2022

Effect of Surface Hydrophobicity on the Adsorption of a Pilus-Derived Adhesin-like Peptide - Yang, Yu; Huang, Jingyuan; Dornbusch, Daniel; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian; Cheung, David L. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Time-Dependent DNA Origami Denaturation by Guanidinium Chloride, Guanidinium Sulfate, and Guanidinium Thiocyanate - Hanke, Marcel; Hansen, Niklas; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (International Journal of Molecular Sciences)
Guanidinium (Gdm) undergoes interactions with both hydrophilic and hydrophobic groups and, thus, is a highly potent denaturant of biomolecular structure. However, our molecular understanding of the interaction of Gdm with proteins and DNA is still rather limited. Here, we investigated the denaturation of DNA origami nanostructures by three Gdm salts, i.e., guanidinium chloride (GdmCl), guanidinium sulfate (Gdm2SO4), and guanidinium thiocyanate (GdmSCN), at different temperatures and in dependence of incubation time. Using DNA origami nanostructures as sensors that translate small molecular transitions into nanostructural changes, the denaturing effects of the Gdm salts were directly visualized by atomic force microscopy. GdmSCN was the most potent DNA denaturant, which caused complete DNA origami denaturation at 50 °C already at a concentration of 2 M. Under such harsh conditions, denaturation occurred within the first 15 min of Gdm exposure, whereas much slower kinetics were observed for the more weakly denaturing salt Gdm2SO4 at 25 °C. Lastly, we observed a novel non-monotonous temperature dependence of DNA origami denaturation in Gdm2SO4 with the fraction of intact nanostructures having an intermediate minimum at about 40 °C. Our results, thus, provide further insights into the highly complex Gdm–DNA interaction and underscore the importance of the counteranion species.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Return to play in elite rugby players after severe knee injuries - Robyn, Aneurin D.; Louw, Quinette A.; Baumeister, Jochen (South African Journal of Physiotherapy)
Background: Medical professionals working in an elite sport environment have the challenging task to balance the athlete’s readiness to return to the playing field after severe injury with other stakeholders’ (coaches, sponsors, teammates) opinions and objectives.Objectives: Our study aimed to evaluate differences in the physical profiles of elite rugby players at return to play (RTP) after a severe knee injury, compared with their pre-injury profiles and matched controls.Method: Before the injury, participants performed four performance tests during their preseason screening. These tests were repeated and compared to baseline once a player was declared fit to play.Results: Significant differences (p ≤ 0.05) were found in the injured players’ group who were slower over 10 m speed, in their decision-making time and the total time of the reactive agility tests at RTP, whilst controls were significantly faster over 10 m and 30 m speed tests. The countermovement jump outcomes showed significant improvement in the uninjured participants (p ≤ 0.05).Conclusion: Our study highlights that injured players’ running speeds and decision-making times are slower after injury. The uninjured players have a positive outcome to training and match stimulus by improving their running speed and lower body explosive power during the season.Clinical implications: Our study provides insight into the RTP profile of elite rugby players, and a novel finding was the decision-making time deficit. This highlights the importance of cognitive training during injury rehabilitation as athletes make numerous decisions in a pressured and uncontrolled environment during a match. Speed training development is recommended as the athletes were slower after severe knee injury.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation

Anti-pattern Detection in Process-Driven Decision Support Systems - Kirchhoff, Jonas; Engels, Gregor (Software Business)
Decision makers increasingly rely on decision support systems for optimal decision making. Recently, special attention has been paid to process-driven decision support systems (PD-DSS) in which a process model prescribes the invocation sequence of software-based decision support services and the data exchange between them. Thus, it is possible to quickly combine available decision support services as needed for optimally supporting the decision making process of an individual decision maker. However, process modelers may accidentally create a process model which is technically well-formed and executable, but contains functional and behavioral flaws such as redundant or missing services. These flaws may result in inefficient computations or invalid decision recommendations when the corresponding PD-DSS is utilized by a decision maker. In this paper, we therefore propose an approach to validate functionality and behavior of a process model representing a PD-DSS. Our approach is based on expressing flaws as anti-patterns for which the process model can be automatically checked via graph matching. We prototypically implemented our approach and demonstrate its applicability in the context of decision making for energy network planning.

Psychological readiness of elite rugby players at return to play after severe knee injury - Robyn, A.D.; Louw, Q.A.; Baumeister, Jochen (African Journal for Physical Activity and Health Sciences (AJPHES))
Keywords: General Medicine

Innovative Leichtbau- und Kühlungskonzepte für elektrische Maschinen durch additive Fertigung (ILuKadd3D) - Haase, Michael; Tasche, Frederik; Bieber, Maximilian; Zibart, Alexander

Contrastive Argument Summarization Using Supervised and Unsupervised Machine Learning - Rieskamp, Jonas
Controversial topics like abortion or capital punishment inherently lack of correct answers or the right way to deal with. Thus, in order to find what is true, what is good, or what should be done, the involved parties need to debate. For the purpose of forming an opinion on a controversial topic someone needs to take in a lot of arguments on that topic to gather information which can be a time-consuming process. To increase efficiency, someone can use an argument search engine to quicken the retrieval of relevant arguments. Although the usage of such a service reduces the time to find arguments, there is still a lot of textual data that needs to be read. To this end, computational summarization approaches for arguments can limit the necessary time for information review by generating short snippets capturing the main gist of each argument. Yet, we suggest that approaches that consider one argument at a time show potential for further improvement in terms of efficiency during information review. In fact, arguments on the same topic, like those retrieved by a search engine for a certain query, partially cover the same content, e. g. arguments regarding the death penalty probably use deterrence as a point in favor of it. However, if the same aspect is central in multiple arguments, their snippets reflect this, which leads to redundancy among the snippets. Consequently, someone interested in gathering information on a controversial topic does not necessarily find new information in each snippet he or she reads. We introduce the task of Contrastive Argument Summarization (CAS) which addresses the aforementioned problem regarding existing argument summarization. An approach that addresses CAS aims to produce contrastive snippets for each argument in a set of topic-related arguments. A contrastive snippet should represent the main gist of its argument, it should account for the argumentative nature of the text, and it should be dissimilar to the other topic-related arguments in order to reduce redundancy among the snippets. We propose two approaches addressing CAS, namely an extended version of the LexRank derivation by Alshomary et al. (2020), and an advancement of the work by Bista et al. (2020). Additionally, we develop two automatic measures to assess to which extent the snippets of one set are opposed. For evaluation, we compile a corpus using the args.me search engine Wachsmuth et al. (2017b) to come close to the suggested area of application. Moreover, we conduct a manual annotation study to assess approaches’ effectiveness. We find that the graph-based approach is superior when it comes to contrastiveness (i. e. snippets being dissimilar to topic-related arguments), and that the second approach outperforms the previous one and the unmodified version of Alshomary et al. (2020) when it comes to representativeness (i. e. snippets capturing the main gist of an argument).

Fair, Individually Rational and Cheap Adjustment - Polevoy, Gleb; Dziubiński, Marcin (Proceedings of the Thirty-First International Joint Conference on Artificial Intelligence)
Consider the practical goal of making a desired action profile played, when the planner can only change the payoffs, bound by stringent constraints. Applications include motivating people to choose the closest school, the closest subway station, or to coordinate on a communication protocol or an investment strategy. Employing subsidies and tolls, we adjust the game so that choosing this predefined action profile becomes strictly dominant. Inspired mainly by the work of Monderer and Tennenholtz, where the promised subsidies do not materialise in the not played profiles, we provide a fair and individually rational game adjustment, such that the total outside investments sum up to zero at any profile, thereby facilitating easy and frequent usage of our adjustment without bearing costs, even if some players behave unexpectedly. The resultant action profile itself needs no adjustment. Importantly, we also prove that our adjustment minimises the general transfer among all such adjustments, counting the total subsidising and taxation.
Keywords: adjustment; strictly dominant; fairness; individually rational; transfer; tax; subsidy

Die professionelle pädagogische Beziehung zwischen Referendar*innen und ihren Seminarlehrkräften: Belastungsfaktor oder Ressource? - Kärner, Tobias; Goller, Michael; Bonnes, Caroline; Maué, Elisabeth (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung: Der Beitrag befasst sich mit der professionellen pädagogischen Beziehung zwischen Referendar*innen und ihren Seminarlehrkräften, deren Beitrag für die Beanspruchung der Referendar*innen bisher noch nicht eingängig untersucht wurde. Das Ziel der Studie ist es, anhand einer Querschnittserhebung von 2583 Referendar*innen und ausgebildeten Lehrkräften, kompensatorische sowie verstärkende Effekte der Beziehungsdimensionen Transparenz, Fairness, Vertrauen und Ambivalenz auf die wahrgenommene Beanspruchung im Referendariat zu untersuchen. Die Analyse erfolgt mittels eines latent moderierten Strukturgleichungsansatzes. Die Ergebnisse zeigen, dass Belastungen durch die Kerntätigkeiten im Referendariat sowie Belastungen durch den Umgang mit Kolleg*innen im Lehrer*innenkollegium in signifikant positivem Zusammenhang mit resultierenden Beanspruchungsreaktionen stehen. Je transparenter, fairer und vertrauensvoller und je weniger ambivalent die Beziehung zur Seminarlehrkraft erlebt wird, desto geringer fallen die Beanspruchungsreaktionen aus. Die Ergebnisse werden hinsichtlich ihrer Relevanz für die Beziehungsarbeit im Referendariat als zentralem Ausbildungsbestandteil der zweiten Phase der Lehrer*innenausbildung diskutiert.
Keywords: Education

Cardinality Constrained Scheduling in Online Models - Epstein, Leah; Lassota, Alexandra; Levin, Asaf; Maack, Marten; Rohwedder, Lars (39th International Symposium on Theoretical Aspects of Computer Science, STACS 2022, March 15-18, 2022, Marseille, France (Virtual Conference))

Clear Roads and Dirty Air? Indirect effects of reduced private traffic congestion on emissions from heavy traffic - Hoffmann, Christin; Thommes, Kirsten (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Clear Roads and Dirty Air? Indirect effects of reduced private traffic congestion on emissions from heavy traffic - Hoffmann, Christin; Thommes, Kirsten (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

The Moral Debater: A Study on the Computational Generation of Morally Framed Arguments - Alshomary, Milad; El Baff, Roxanne; Gurcke, Timon; Wachsmuth, Henning (Proceedings of the 60th Annual Meeting of the Association for Computational Linguistics)

"Mama Always Had a Way of Explaining Things So I Could Understand": A Dialogue Corpus for Learning How to Explain - Wachsmuth, Henning; Alshomary, Milad (Proceedings of the 29th International Conference on Computational Linguistics)

On the Role of Knowledge in Computational Argumentation - Lauscher, Anne; Wachsmuth, Henning; Gurevych, Iryna; Glavaš, Goran (Transactions of the Association for Computational Linguistics)

Identifying the Human Values behind Arguments - Kiesel, Johannes; Alshomary, Milad; Handke, Nicolas; Cai, Xiaoni; Wachsmuth, Henning; Stein, Benno (Proceedings of the 60th Annual Meeting of the Association for Computational Linguistics)

Domain-specific Language for Condition Monitoring Software Development - Pasic, Faruk; Becker, Matthias (2022 IEEE 27th International Conference on Emerging Technologies and Factory Automation (ETFA))

"Swer siner kunst meister ist, der hat gewalt an siner list". Herborts von Fritzlar Liet von Troye als Fortsetzungstext des Eneasromans Heinrichs von Veldeke am Schnittpunkt von Aneignung und Neukonstitution - Somogyi, Peter (Troja bauen)

No Word Embedding Model Is Perfect: Evaluating the Representation Accuracy for Social Bias in the Media - Spliethöver, Maximilian; Keiff, Maximilian; Wachsmuth, Henning (Proceedings of The 2022 Conference on Empirical Methods in Natural Language Processing (EMNLP 2022))
News articles both shape and reflect public opinion across the political spectrum. Analyzing them for social bias can thus provide valuable insights, such as prevailing stereotypes in society and the media, which are often adopted by NLP models trained on respective data. Recent work has relied on word embedding bias measures, such as WEAT. However, several representation issues of embeddings can harm the measures' accuracy, including low-resource settings and token frequency differences. In this work, we study what kind of embedding algorithm serves best to accurately measure types of social bias known to exist in US online news articles. To cover the whole spectrum of political bias in the US, we collect 500k articles and review psychology literature with respect to expected social bias. We then quantify social bias using WEAT along with embedding algorithms that account for the aforementioned issues. We compare how models trained with the algorithms on news articles represent the expected social bias. Our results suggest that the standard way to quantify bias does not align well with knowledge from psychology. While the proposed algorithms reduce the~gap, they still do not fully match the literature.

Pfirsichbaum und dunkler Wald. Pflanzliche Konfigurationen zwischen Dynamisierung und Innehalten in 'Partonopier und Meliur' Konrads von Würzburg - Musiol, Marie-Luise; Winst, Silke (Spiritual Vegetation: Vegetal Nature in Religious Contexts Across Medieval and Early Modern Europe (Berliner Mittelalter- und Frühneuzeitforschung, Vol. 26))

Bennewitz, Ingrid/Eming, Jutta/Traulsen, Johannes: Gender Studies – Queer Studies – Intersektionalität. Eine Zwischenbilanz aus mediävistischer Perspektive (Berliner Mittelalter- und Frühneuzeitforschung 25), Göttingen 2019 - Musiol, Marie-Luise (Sexuologie)

Menschlicher Körper, heiliger Körper. Zur Kreuzigung Christi im Donaueschinger Passionsspiel - Musiol, Marie-Luise (Unverfügbar. Kulturen des Heiligen)

Can Tax Rate Changes Accelerate Investment under Entry and Exit Flexibility? – Insights from an Economic Experiment - Fahr, René; Janssen, Elmar A.; Sureth-Sloane, Caren (FinanzArchiv / Public Finance Analysis)
This study investigates the conditions under which tax rate changes accelerate risky investments. While tax rate increases are often expected to harm investment, analytical studies find tax rate increases may foster investment under flexibility.We design a theorybased experimentwith a binomial random walk and entry–exit flexibility.We find accelerated investment upon tax rate increases irrespective of an exit option, but no corresponding response to tax cuts. This asymmetry may be due to tax salience and mechanisms from irreversible choice under uncertainty. Given this evidence of unexpected tax-reform effects, tax policymakers should carefully consider behavioral aspects.
Keywords: Economic ExperimentM; Investment Decisions; Tax Effects; Timing Flexibility; Uncertainty

How Does Trust Affect Concessionary Behavior in Tax Bargaining? - Eberhartinger, Eva; Speitmann, Raffael; Sureth-Sloane, Caren; Wu, Yuchen (FinanzArchiv / Public Finance Analysis)
We study the bargaining behavior between auditor and auditee in a tax setting and scrutinize the effect of interpersonal trust and trust in government on both parties’ concessions. We find evidence that both kinds of trust affect the concessionary behavior, albeit in different ways. While trust in government affects concessionary behavior in line with intuitive predictions, we find that interpersonal trust only affects tax auditors. For high interpersonal trust, the alleviating effect of high trust in government on tax auditors’ concessions is less pronounced. Our findings help tax authorities to shape programs to enhance compliance in an atmosphere of trust.
Keywords: Behavioral Taxation; Concessionary Behavior; Interpersonal Trust; Tax Audit; Trust in Government

Schlieren imaging with fractional Fourier transform to visualise ultrasonic fields - Hetkämper, Tim; Claes, Leander; Henning, Bernd (Sensoren und Messsysteme - Beiträge der 21. ITG/GMA-Fachtagung)

Back to the Roots: Predicting the Source Domain of Metaphors using Contrastive Learning - Sengupta, Meghdut; Alshomary, Milad; Wachsmuth, Henning (Proceedings of the 2022 Workshop on Figurative Language Processing)

Overview of Touché 2022: Argument Retrieval - Bondarenko, Alexander; Fröbe, Maik; Kiesel, Johannes; Syed, Shahbaz; Gurcke, Timon; Beloucif, Meriem; Panchenko, Alexander; Biemann, Chris; Stein, Benno; Wachsmuth, Henning; Potthast, Martin; Hagen, Matthias (Lecture Notes in Computer Science)

Augmented Reality Anwendungen in der betrieblichen Aus‐ und Weiterbildung - Kärner, Tobias; Goller, Michael; Maier, Andreas (Digitalisierung und digitale Medien in der Berufsbildung: Konzepte, Befunde und Herausforderungen)
Der Beitrag widmet sich dem Einsatz von Augmented Reality (AR) in betrieblichen Aus- und Weiterbildungskontexten. Hierbei stehen insbesondere Fragen zu Berufsfeldern und Ausbildungsinhalten, zu verwendeten AR-Spezifikationen, zu Zusammenhängen zwischen AR-Anwendung und leistungs-, wahrnehmungs- und motivationsbezogenen Variablen sowie zur didaktischen Einbettung entsprechender Technologien im Fokus. Auf Basis einer integrierenden Sichtung bestehender Literatur konnten insgesamt 16 Studien sowie zwei bereits vorliegende Literaturreviews in die Analyse eingeschlossen werden. Die Ergebnisse verweisen u. a. auf eine heterogene Lage hinsichtlich forschungsmethodischer Zugänge und didaktischer Referenzkonzepte. Weitgehend förderliche Effekte auf leistungs-, wahrnehmungs- und motivationsbezogene Variablen stimmen insgesamt bezüglich des AR-Einsatzes positiv, machen aber auch die Notwendigkeit einer integrierten Betrachtung technologischer und pädagogisch-instruktionaler Gestaltungsparameter deutlich.
Keywords: Augmented Reality; Ausbildung; Weiterbildung; Lernen mit digitalen Medien; integratives Literaturreview

Kompetenzen des betrieblichen Ausbildungspersonals: Eine literaturbasierte Systematisierung - Bonnes, Caroline; Binkert, Julia; Goller, Michael (Berufsbildung in Wissenschaft und Praxis – BWP)
Startpunkt jeglicher Professionalisierungsbemühungen ist ein Verständnis der für das professionelle Handeln notwendigen Kompetenzen. Dieser Beitrag widmet sich der literaturbasierten Identifikation von Kompetenzen des betrieblichen Ausbildungspersonals und ordnet diese den vier Kompetenzbereichen Fach-, Methoden-, Sozial- und Selbstkompetenz zu. Die Ergebnisse können sowohl als Grundlage für weitere Forschung dienen als auch in der Praxis als Orientierung für die Gestaltung von Qualifizierungsmaßnahmen verwendet werden.

Argument Novelty and Validity Assessment via Multitask and Transfer Learning - Alshomary, Milad; Stahl, Maja (Proceedings of the 9th Workshop on Argument Mining)
An argument is a constellation of premises reasoning towards a certain conclusion. The automatic generation of conclusions is becoming a very prominent task, raising the need for automatic measures to assess the quality of these generated conclusions. The SharedTask at the 9th Workshop on Argument Mining proposes a new task to assess the novelty and validity of a conclusion given a set of premises. In this paper, we present a multitask learning approach that transfers the knowledge learned from the natural language inference task to the tasks at hand. Evaluation results indicate the importance of both knowledge transfer and joint learning, placing our approach in the fifth place with strong results compared to baselines.

Multimodal quantification of degradation pathways during extreme fast charging of lithium-ion batteries - McShane, Eric J.; Paul, Partha P.; Tanim, Tanvir R.; Cao, Chuntian; Steinrück, Hans-Georg; Thampy, Vivek; Trask, Stephen E.; Dunlop, Alison R.; Jansen, Andrew N.; Dufek, Eric J.; Toney, Michael F.; Weker, Johanna Nelson; et al. (Journal of Materials Chemistry A)
Using a unique combination of advanced characterization techniques, we identify specific degradation mechanisms and quantify degradative species formed during fast charge cycling of lithium-ion battery pouch cells.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Simultaneous neutron and X-ray tomography for visualization of graphite electrode degradation in fast-charged lithium-ion batteries - Yusuf, Maha; LaManna, Jacob M.; Paul, Partha P.; Agyeman-Budu, David N.; Cao, Chuntian; Dunlop, Alison R.; Jansen, Andrew N.; Polzin, Bryant J.; Trask, Stephen E.; Tanim, Tanvir R.; Dufek, Eric J.; Thampy, Vivek; et al. (Cell Reports Physical Science)
Keywords: General Physics and Astronomy; General Energy; General Engineering; General Materials Science; General Chemistry

HARRIS: Hybrid Ranking and Regression Forests for Algorithm Selection - Fehring, Lukass; Hanselle, Jonas Manuel; Tornede, Alexander (Workshop on Meta-Learning (MetaLearn 2022) @ NeurIPS 2022)
It is well known that different algorithms perform differently well on an instance of an algorithmic problem, motivating algorithm selection (AS): Given an instance of an algorithmic problem, which is the most suitable algorithm to solve it? As such, the AS problem has received considerable attention resulting in various approaches - many of which either solve a regression or ranking problem under the hood. Although both of these formulations yield very natural ways to tackle AS, they have considerable weaknesses. On the one hand, correctly predicting the performance of an algorithm on an instance is a sufficient, but not a necessary condition to produce a correct ranking over algorithms and in particular ranking the best algorithm first. On the other hand, classical ranking approaches often do not account for concrete performance values available in the training data, but only leverage rankings composed from such data. We propose HARRIS- Hybrid rAnking and RegRessIon foreSts - a new algorithm selector leveraging special forests, combining the strengths of both approaches while alleviating their weaknesses. HARRIS' decisions are based on a forest model, whose trees are created based on splits optimized on a hybrid ranking and regression loss function. As our preliminary experimental study on ASLib shows, HARRIS improves over standard algorithm selection approaches on some scenarios showing that combining ranking and regression in trees is indeed promising for AS.

Methoden zum Design digitaler Plattformen, Geschäftsmodelle und Service-Ökosysteme - Robra-Bissantz, Susanne; Lattemann, Christoph; Laue, Ralf; Leonhard-Pfleger, Raphaela; Wagner, Luisa; Gerundt, Oliver; Schlimbach, Ricarda; Baumann, Sabine; Vorbohle, Christian; Gottschalk, Sebastian; Kundisch, Dennis; Engels, Gregor; et al. (HMD Praxis der Wirtschaftsinformatik)

Tackling Crises Together? – An Econometric Analysis of Charitable Crowdfunding During the COVID-19 Pandemic - Althaus, Maike; Poniatowski, Martin; Kundisch, Dennis (Proceedings of the 43rd International Conference on Information Systems (ICIS))

May I have your attention, please? Analyzing the effects of attention screening mechanisms on crowdworking platforms - Laux, Florian; Poniatowski, Martin; Kundisch, Dennis

Online Reviews in B2B Markets: A Qualitative Study on the Underlying Motives - Seutter, Janina

The Structural Power of Reconfigurable Circuits in the Amoebot Model - Padalkin, Andreas; Scheideler, Christian; Warner, Daniel (28th International Conference on DNA Computing and Molecular Programming (DNA 28))

Fault-Tolerant Shape Formation in the Amoebot Model - Kostitsyna, Irina; Scheideler, Christian; Warner, Daniel (28th International Conference on DNA Computing and Molecular Programming (DNA 28))

Online Reviews in B2B Markets: A Qualitative Study of Underlying Motivations - Seutter, Janina (Proceedings of the 30th European Conference on Information Systems (ECIS))

How the Display of the Transaction Count Affects the Purchase Intention - Poniatowski, Martin (Proceedings of the 28th Americas Conference on Information Systems (AMCIS))

Static data-flow analysis for software product lines in C - Schubert, Philipp; Gazzillo, Paul; Patterson, Zach; Braha, Julian; Schiebel, Fabian; Hermann, Ben; Wei, Shiyi; Bodden, Eric (Automated Software Engineering)
Abstract Many critical codebases are written in C, and most of them use preprocessor directives to encode variability, effectively encoding software product lines. These preprocessor directives, however, challenge any static code analysis. SPLlift, a previously presented approach for analyzing software product lines, is limited to Java programs that use a rather simple feature encoding and to analysis problems with a finite and ideally small domain. Other approaches that allow the analysis of real-world C software product lines use special-purpose analyses, preventing the reuse of existing analysis infrastructures and ignoring the progress made by the static analysis community. This work presents VarAlyzer , a novel static analysis approach for software product lines. VarAlyzer first transforms preprocessor constructs to plain C while preserving their variability and semantics. It then solves any given distributive analysis problem on transformed product lines in a variability-aware manner. VarAlyzer ’s analysis results are annotated with feature constraints that encode in which configurations each result holds. Our experiments with 95 compilation units of OpenSSL show that applying VarAlyzer enables one to conduct inter-procedural, flow-, field- and context-sensitive data-flow analyses on entire product lines for the first time, outperforming the product-based approach for highly-configurable systems.
Keywords: inter-procedural static analysis; software product lines; preprocessor; LLVM; C/C++

Overcoming Silos: A Review of Business Model Modeling Languages for Business Ecosystems - Vorbohle, Christian; Kundisch, Dennis (Proceedings of the 30th European Conference on Information Systems (ECIS))